2014
DOI: 10.1103/physrevb.89.134427
|View full text |Cite
|
Sign up to set email alerts
|

Switching field distributions with spin transfer torques in perpendicularly magnetized spin-valve nanopillars

Abstract: We present switching field distributions of spin-transfer-assisted magnetization reversal in perpendicularly magnetized Co/Ni multilayer spin-valve nanopillars at room temperature. Switching field measurements of the Co/Ni free layer of spin-valve nanopillars with a 50 nm × 300 nm ellipse cross section were conducted as a function of current. The validity of a model that assumes a spin-current-dependent effective barrier for thermally activated reversal is tested by measuring switching field distributions unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Solving Eqs. (19) and (20) with respect to f b and θ d , we found that the frequency determining the boundary between region 1 and region 2 is given by…”
Section: Optimized Frequency and Minimized Switching Currentmentioning
confidence: 80%
“…Solving Eqs. (19) and (20) with respect to f b and θ d , we found that the frequency determining the boundary between region 1 and region 2 is given by…”
Section: Optimized Frequency and Minimized Switching Currentmentioning
confidence: 80%
“…27,36 Therefore, it is important to study clustering in highly anisotropic shapes, such as ellipses, used also as sample shapes in other magnetic materials, such as nanopillars. 37 Moreover, the study of ellipses is useful as different points on their surface are characterized by different radii of curvature, with the smallest ones at vertices corresponding to the corners of hexagonal/ rectangular systems and the largest ones at co-vertices, approaching infinity for elongated ellipses and then corresponding to linear edges. In addition, the control of the eccentricity of ellipses enables one to study systems with shapes changing from circular to needles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such devices would be able to generate oscillations requiring low or even zero external magnetic fields [13][14][15][16][17]. Given this context, this dissertation is focused on the exploration of innovated magnetic multilayers systems utilizing PMA materials with an ultimate goal to lower the switching current density of STT devices and to create coherent oscillation with output powers larger than 0.5W.…”
Section: Motivationmentioning
confidence: 99%
“…Moreover, the low damping constant of MnAl (~0.006) [84] is very desirable for low energy dissipation spin torque devices such as spin-transfer torque magnetic tunnel junctions and spin torque nano-oscillators (STNO) [85]. Typically STNO operation requires very large external magnetic fields, however recent innovation utilizing PMA materials has made it possible to operate at low field or even at zero field [13][14][15][16][17].…”
Section: L1 0 Mnalmentioning
confidence: 99%
See 1 more Smart Citation